Synthesis, Characterization and Biological Evaluation of Halolitoralin B - A Natural Cyclic Peptide - DAHIYA, RAJIV; PATHAK, DEVENDER (Asian Journal of Chemistry, 2010)
A new potent bioactive cyclic tetrapeptide halolitoralin B (7) has been synthesized by solution phase technique which was previously isolated from the marine sediment-derived bacterial strain Halobacillus litoralis YS3106. The structure of the peptide was characterized by IR, 1H NMR, 13C NMR, FAB MS spectral data as well as elemental analysis. Synthesized cyclopeptide was also screened for its antimicrobial and anthelmintic activities and found to exhibit potent antifungal activity against pathogenic fungi Candida albicans along with potent anthelmintic activity against earthworms Megascoplex konkanensis and Eudrilus sp. In addition, peptide was also found to exhibit moderate antibacterial activity against gram negative bacteria Pseudomonas aeruginosa and Escherichia coli. Gram positive bacteria were found to be resistant towards the newly synthesized peptide.